Legal Norms and Child Welfare: A Review of Child Health Policy in the Era of Globalization - Setiawan, Leonathan; Yea, Maria Oce; Prayuti, Yuyut (Dinasti Research, 2025)
In the era of globalization, child welfare has become a major focus of national and international policies. Legal norms play an important role in ensuring children's basic rights, especially in the health sector. This article analyzes the role of legal norms in child health policy and its impact. The method used by the researcher is a descriptive-analytical literature review, which explores various regulations and policies in various countries. Increasingly complex child health challenges due to social and economic changes demand more responsive and human rights-based policies. Child protection in law is described in Welfare Theory, Human Rights Theory and Legal Protection Theory. The successful implementation of the law is described in the Law Enforcement Effectiveness Theory. In Indonesia, the gap between regulation and implementation of child health policies, accessibility of health services, community education, and social economic support are crucial aspects. There is a need for synergy from government, organizations and communities to create a more inclusive and sustainable child health policy.